N-Acetylcysteine as a Bacterial Antibiofilm Adjuvant: Mechanisms, Synergistic Combinations and Clinical Translation - Anastasia N. Golub; Natalia N. Mikhailova; Maria V. Pomytkina; Ksenia V. Eremeeva; Elena A. Shevchik; Galina N. Nikiforova; Valeriy M. Svistushkin; Vera V. Korennaya; Yuriy L. Vasil’ev; Elena O. Bakhrushina (Life, 2026)
N-acetylcysteine (NAC) is a synthetic derivative of L-cysteine, known since the mid-20th century as a mucolytic agent and, in recent decades, has attracted attention for its antioxidant and antibiofilm properties. Bacterial biofilms are structured communities of microorganisms enclosed in an extracellular polymeric matrix, which accounts for their markedly increased resistance to antibiotics (up to 1000-fold higher than in planktonic forms) and to the host immune response. According to the literature, up to 65% of infectious agents are associated with biofilm formation, making them a challenging therapeutic target. This review systematizes current data on the molecular mechanisms of the antibiofilm action of NAC, including disruption of matrix proteins and polysaccharides, degradation of extracellular DNA, suppression of the quorum sensing system, and disturbance of bacterial redox homeostasis. Particular attention is given to synergistic combinations of NAC with antibiotics of five major classes; effective concentrations are provided, and the types of interaction are characterized. The results of clinical studies from the last decade are reviewed, demonstrating the potential of NAC as an adjuvant in urinary tract infections, chronic rhinosinusitis, diabetic osteomyelitis, and cystic fibrosis. The main limitations (pH dependence, instability, low oral bioavailability) are critically evaluated, and approaches to overcoming them using nanoparticles, hydrogels, and combinations with propolis or chitosan are proposed. The review is intended for researchers in antimicrobial chemotherapy and developers of new drug delivery systems.